THE EFFECT OF CORPORATE GOVERNANCE, COMPANY CHARACTERISTICS, AND FINANCIAL DISTRESS ON EARNINGS MANAGEMENT IN INDUSTRIAL COMPANIES (2022–2024) - Mohammad Fajar Fahrizky; Indah Fajarini Sri Wahyuningrum (PT. Radja Intercontinental Publishing, 2026)
This study aims to examine and analyze the influence of corporate governance mechanisms proxied by institutional ownership, audit committee meetings, independent commissioners, audit gender, and commissioner gender and financial characteristics proxied by Debt to Equity Ratio (DER) and Return on Assets (ROA) along with financial distress on earnings management practices. The population of this research consists of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Using a purposive sampling method, a sample of 62 companies was selected, yielding a total of 186 panel data observations analyzed using multiple linear regression via EViews software. The partial empirical results demonstrate that all independent variables have no significant effect on earnings management, except for Return on Assets (ROA), which has a significant negative effect on earnings management. The limitation of this study lies in its narrow focus on the industrial sector for the 2022-2024 period, the reliance on a single discretionary accrual proxy, and corporate governance indicators that are still structurally quantity-oriented. Therefore, future research is suggested to expand the multi-sector scope of listed companies, utilize a Real Earnings Management (REM) proxy, and integrate aspects of quality competence in educational backgrounds as well as the personal integrity of supervisors.